3(8х – 6) = 4(6х – 4,5)
2(3х – 8) – (6х + 1) = 7
7х + 9 = 100
9 +13х = 35 + 26х
0,6х + 1,7 = 0,3х – 1,3
х/6 - 0,82 = 3х очень Нужно всё расписать, не только ответ.

Пингвинено25 Пингвинено25    3   22.04.2020 14:54    0

Ответы
Fateev20067 Fateev20067  22.04.2020 15:30

Пошаговое объяснение:

1) 15х+10=6х-8

15х-6х=-10-8

9х=-18

х=-18:9=2

ответ: 2.

2) -2(х-4)=3+7х

-2х+8=3+7х

-2х-7х=-8+3

-9х=-5

х=5/9

ответ: 5/9.

3) 26х-6=8х-42

26х-8х=6-42

18х=-36

х=-36:18=-2

ответ: -2.

4) 10х-8=20х+74

10х-20х=8+74

-10х=82

х=82:(-10)=-8,2

ответ: -8,2.

5) 13х+8=27х+18

13х-27х=-8+18

-14х=10

х=10:14=5/7

ответ: 5/7.

Подробнее - на -

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика